2002
DOI: 10.1145/964725.633040
|View full text |Cite
|
Sign up to set email alerts
|

Network topology generators

Abstract: Following the long-held belief that the Internet is hierarchical, the network topology generators most widely used by the Internet research community, Transit-Stub and Tiers, create networks with a deliberately hierarchical structure. However, in 1999 a seminal paper by Faloutsos et al. revealed that the Internet's degree distribution is a power-law. Because the degree distributions produced by the Transit-Stub and Tiers generators are not power-laws, the research community has largely dismissed them as inadeq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 85 publications
(25 citation statements)
references
References 26 publications
0
22
0
Order By: Relevance
“…In a seminal paper [22], Faloutsos et al have shown that the degree distribution of autonomous systems in Internet follows a power law with power exponent τ ≈ 2.2. Thus, the power law random graph with this value of τ can possibly lead to a good Internet model on the autonomous systems (AS) level (see [22,38]). For the Internet on the more detailed router level, extensive measurements exist for the hopcount, which is the number of routers traversed between two typical routers, as well as for the AS-count, which is the number of autonomous systems traversed between two typical routers.…”
Section: Methodology and Heuristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a seminal paper [22], Faloutsos et al have shown that the degree distribution of autonomous systems in Internet follows a power law with power exponent τ ≈ 2.2. Thus, the power law random graph with this value of τ can possibly lead to a good Internet model on the autonomous systems (AS) level (see [22,38]). For the Internet on the more detailed router level, extensive measurements exist for the hopcount, which is the number of routers traversed between two typical routers, as well as for the AS-count, which is the number of autonomous systems traversed between two typical routers.…”
Section: Methodology and Heuristicsmentioning
confidence: 99%
“…In [38], and inspired by the observed power law degree sequence in [22], the configuration model with i.i.d. degrees is proposed as a model for the AS-graph in Internet, and it is argued on a qualitative basis that this simple model serves as a better model for the Internet topology than currently used topology generators.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The generators either use ''biased'' or preferential growth policy [2,5,8,16,35] or force a power law degree distribution [1,24]. These constructive method produce synthetic graphs by focusing on matching their degree distributions with that of real Internet instances, and they often fail to match other topological properties, as multiply documented in [8,12,22,24,45].…”
Section: Introductionmentioning
confidence: 99%
“…The weakness of these constructive methods lies in their dependence on the principles of construction, and the choice of parameter values. Furthermore, several of them focus on matching the degree distribution, while they often fail to match other topological properties, as multiply documented [5] [7] [15] [16] [29].…”
Section: Introductionmentioning
confidence: 99%